2017
DOI: 10.1371/journal.pone.0181918
|View full text |Cite
|
Sign up to set email alerts
|

Proposed equations and reference values for calculating bone health in children and adolescent based on age and sex

Abstract: BackgroundThe Dual Energy X-Ray Absorptiometry (DXA) is the gold standard for measuring BMD and bone mineral content (BMC). In general, DXA is ideal for pediatric use. However, the development of specific standards for particular geographic regions limits its use and application for certain socio-cultural contexts. Additionally, the anthropometry may be a low cost and easy to use alternative method in epidemiological contexts. The goal of our study was to develop regression equations for predicting bone health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
3
9
0
8
Order By: Relevance
“…The predictors of the BMD, weight, length of the foot, and diameter of the humerus were the variables that showed high predictive values in goalkeepers and field players. These results are consistent with other studies conducted with non-athletic children and adolescents (Silva et al, 2006; Fonseca et al, 2008; Gómez-Campos et al, 2017). In addition, the results demonstrated that anthropometric variables that are routinely assessed in the field are necessary to use to analyze bone health in children and adolescents.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The predictors of the BMD, weight, length of the foot, and diameter of the humerus were the variables that showed high predictive values in goalkeepers and field players. These results are consistent with other studies conducted with non-athletic children and adolescents (Silva et al, 2006; Fonseca et al, 2008; Gómez-Campos et al, 2017). In addition, the results demonstrated that anthropometric variables that are routinely assessed in the field are necessary to use to analyze bone health in children and adolescents.…”
Section: Discussionsupporting
confidence: 93%
“…This ensured a high precision in the equations proposed for both working groups. In addition, some previous studies have reported similar R 2 values and levels of agreement for samples of children and adolescents (Cameron et al, 2004; Cossio-Bolaños et al, 2017; Gómez-Campos et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The results indicated an excellent level of agreement (CCC = 0.90–0.93) according to Lin's index (18). In addition, the precision and accuracy described the DRI were similar to those of other studies that have developed regression equations for body composition based on anthropometric variables (11, 22).…”
Section: Discussionsupporting
confidence: 75%
“…These indicators together may specifically be adjusted to each body size to more accurately identify the LM. Moreover, it may be a low cost and easy to use alternate method in epidemiological contexts (11).…”
Section: Introductionmentioning
confidence: 99%